2019
DOI: 10.1504/ijicbm.2019.096925
|View full text |Cite
|
Sign up to set email alerts
|

Role of financial knowledge, financial socialisation and financial risk attitude in financial satisfaction of Indian individuals

Abstract: The purpose of the present study is to examine the influence of financial knowledge and financial socialisation on financial satisfaction of an individual with financial risk attitude as a mediator with special focus on tier II city of India. The authors have adapted scales from literature on financial knowledge, financial socialisation, financial risk attitude and financial satisfaction to create a questionnaire. The mediated regression analysis was performed to test hypothesised relationships. Significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…In most of the studies, financial risk tolerance attitude acts as a mediator between certain variables. Study reveals that "the relationship between financial socialization and financial satisfaction with financial risk attitude as mediator were also found to be significantly positive" (Saurabh & Nandan, 2019). Further, this study also reveals that financial risk attitude shows mediating between financial knowledge and financial satisfaction".…”
Section: Mediating Role Of Speculative Riskmentioning
confidence: 59%
See 1 more Smart Citation
“…In most of the studies, financial risk tolerance attitude acts as a mediator between certain variables. Study reveals that "the relationship between financial socialization and financial satisfaction with financial risk attitude as mediator were also found to be significantly positive" (Saurabh & Nandan, 2019). Further, this study also reveals that financial risk attitude shows mediating between financial knowledge and financial satisfaction".…”
Section: Mediating Role Of Speculative Riskmentioning
confidence: 59%
“…Payne et al, (2014) noted that financial socialization has a significant impact on financial satisfaction. Saurabh and Nandan (2019) reveal that individuals rely on their family from the infant level and this affiliation influences their thinking process, attitude, and decision making especially in the matter of finance. They further conclude that individuals who perceive themselves as knowledgeable are also inclined by family, peers, and media toward their financial satisfaction.…”
Section: Financial Socialisation and Financial Satisfactionmentioning
confidence: 99%
“…In terms of nuclear power popularization, the higher the level of subjective knowledge, the higher the acceptance of nuclear power risks [60,61], and the lower the willingness to evade. In the financial scenario, financial knowledge was positively correlated with risk preference attitude, and risk preference attitude positively affected financial market participation [62][63][64]. Risk preference attitude was a significant mediating variable.…”
Section: Impact Of Risk Knowledge On Risk Aversion Attitudementioning
confidence: 99%
“…Preference of the methods of investment of an individual resulted from a desire to achieve a specific financial goal and thus financial satisfaction. 24 From the results of this study, it was found that the preferred investment option for Indian doctors was a savings account followed closely by medical insurance and other (gold, shares, or land). Thus we can say that the attitude of Indian doctors towards finances was such that they looked for secure options or options that can avail them long term security in terms of finances.…”
Section: Discussionmentioning
confidence: 79%
“…Based on a previous study by global financial literacy excellence center that stated the financial literacy among Indians was 24%, the sample size for our study was calculated as 281. 24 However, our final sample size was 286 (N=286). Out of the 286 study participants, 179 were males and 106 were females and 1 person preferred not to disclose their gender.…”
Section: Study Population and Sample Sizementioning
confidence: 99%